Application of Personal Branding As a Campus “Bela Negara” at UPN “Veteran” East Java - E. Poernomo; R. Hidayat; R. R. Prayogo (Nusantara Science and Technology Proceedings)
The application of personal branding has become a central element in new management practices throughout the University. Personal branding plays a role in shaping the differentiation produced by a university. Personal branding is considered important for the sustainability of an organization in introducing brands in the community. Some organizations continue to improve and introduce personal branding, including universities in Indonesia. One of the higher education that has strong personal branding is the East Java National Development University 'UPN' East Java. UPN "Veteran" East Java as a Campus “Bela Negara” that emphasizes the values of defending the country as a good citizen to be applied in universities. Various theories and literature approach, applying positive personal branding can be influenced by institution image, institution reputation, and social media. The purpose of the study was to see how many institutions image, institution reputation, and social media influence the personal branding owned by UPN "Veteran" East Java. The sample in this study were students who chose to study in the Study Program of FISIP Business Administration UPN "Veteran" East Java as many as 200 respondents, with a sampling technique method that is purposive sampling. Data analysis uses a model structure (PLS-SEM) with smart pls that are used to test the relationship and influence between research variables. The results of this research show that institution image is positively and significantly related to institution reputation but insignificant on personal branding. On the other hand, the institution reputation is positively and significantly related to personal branding and social media owned by universities can influence personal branding.